Preventive effects of iontophoresis on bovine enamel decalcification through enhancing uptake and transportation of fluoride -in vitro study. Issue 2 (August 2018) - Tanaka, Toshiko; Saito, Ayaka; Watanabe, Koji; Saeki, Katsura; Nakashima, Hideaki; Maki, Kenshi
Abstract: Background: Topical fluoride application has been performed all over the world especially in the field of Pediatric Dentistry to prevent enamel decalcification. However, the effect of the method against demineralization has not been sufficiently reported yet. This study was performed to evaluate the effectiveness of the method by measuring the uptake amount of fluorine (F) into enamel, and also to investigate the relationship between the amount of F incorporated and the decalcification depth. Methods: Bovine incisors were immersed in 2% fluoride solution in the absence (the immersion method) or presence (the iontophoresis method) of iontophoresis. Sample teeth were then decalcified in 0.1 M lactic acid solution. The F concentration was measured using a fluorine ion meter, while atomic absorption spectrophotometry was used to determine calcium (Ca) concentrations. Results: When the decalcification time was 15 min, the uptake of F was significantly higher in the iontophoresis method than in the immersion method. Furthermore, the decalcification depth was markedly shallower with the iontophoresis method than with the immersion method. In immersion method, no changes were observed in the uptake of F between decalcification times of 5 and 15 min regardless of immersion times. F uptake levels were dependent on the current-carrying time. A clear inverse correlation was observed between F uptake levels and the decalcification depth (r = 0.967). Conclusions: Iontophoresis increased the uptake of F and enhanced its penetration into the enamel, thereby decreasing decalcification by acid. The study showed the effectiveness of the Iontophoresis method.